El arte de escribir, el yo poético y las instancias creativas - Gonzáles Márquez, Carla Vanessa (2019)
The purpose of this work is to define what creative writing is and describe the processes since the moment the writer build the fictional universes which is part of a literary work: a tale, a novel or a poem. Also, to define de existence of a poetic “I” as a discursive subject in the lyric fiction universe.